Periodicity on Nicholson's blowflies systems involving patch structure and mortality terms. Issue 3 (3rd May 2020) - Ding, Hui-Sheng; Fu, Si
ABSTRACT: In this paper, we investigate a class of delayed Nicholson's blowflies systems with patch structure and nonlinear density-dependent mortality terms. By using differential inequality approach and Lyapunov function method, some criteria are established for the existence, uniqueness and exponential stability of positive periodic solutions for the addressed systems. Finally, we give a numerical example to illustrate the effectiveness and feasibility of the obtain results.